2011
DOI: 10.1158/1535-7163.mct-10-0415
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib Can Induce Vascular Endothelial Growth Factor Expression and Tumor Angiogenesis

Abstract: Increased COX-2

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…For example, PTEN phosphorylation appears to be upregulated in leukemia cancer cells compared to normal thymocytes through decreased CK2 expression and activity [32]. Increased PTEN phosphorylation at Ser-380 has also been observed in gastric tumors, and Notch signaling appears to regulate PTEN phosphorylation in pancreatic cancer cells [63, 64]. This provides a mechanism of PTEN inactivation in cancers where no loss of PTEN expression is observed.…”
Section: Pten Regulation By Post-translational Modificationsmentioning
confidence: 99%
“…For example, PTEN phosphorylation appears to be upregulated in leukemia cancer cells compared to normal thymocytes through decreased CK2 expression and activity [32]. Increased PTEN phosphorylation at Ser-380 has also been observed in gastric tumors, and Notch signaling appears to regulate PTEN phosphorylation in pancreatic cancer cells [63, 64]. This provides a mechanism of PTEN inactivation in cancers where no loss of PTEN expression is observed.…”
Section: Pten Regulation By Post-translational Modificationsmentioning
confidence: 99%
“…In this context Wei et al reported in 2004 that celecoxib inhibits VEGF expression and reduces angiogenesis and metastasis of human pancreatic cancer via suppression of Sp1 transcription factor activity (Wei et al, 2004). Additionally, and in contrast to its previously mentioned anti-angiogenic profile, researchers have shown that celecoxib can induce VEGF expression and tumor angiogenesis (Xu et al, 2011). …”
Section: Pyrazoles Synthesismentioning
confidence: 93%
“…Flank tumor frozen sections (5 μm) were fixed in cold methanol and stained with rat anti-mouse CD31 monoclonal antibody (BD Biosciences) as previously described [47]. CD31-stained slides were observed by fluorescent microscopy and images captured by an associated digital camera.…”
Section: Methodsmentioning
confidence: 99%